Feasible products and cost indicators for vapour-liquid equilibrium separation processes - Jobson, Megan Ruth (My University, 1996)
The aim of process synthesis is to select process equipment and interconnections in order to achieve some performance goal, such as the composition of one or more products, in an optimal manner. This work focuses on the synthesis and optimization of vapour-liquid equilibrium (VLE) separation processes. The regions of feasible products for a range of VLE separation processes (including simple distillation, simple condensation and processes comprised of one or two flash stages and mixing) are determined and analyzed. Binary and ternary systems, both ideal and non-ideal, are considered. It is shows .at the products of VLE separation processes are not inherently restricted; limitations in product composition are therefore introduced by the choice of separation equipment. The products on the boundary of the region of feasible products are often found to be associated with infinite costs. Therefore costs and, product composition should he considered simultaneously in process synthesis. This work introduces a pair of variables which are proposed as cost indicators for VLE separation processes. These variables, which are called "capacity variables", pertain to distillation columns and a wide range of other VLE separation processes, allowing their comparison. The variables incorporate both capital and energy costs of a process and are thus related to total annual costs. They accommodate costs of both boiling and condensing. They ate simple to calculate from the mass balance equations. The capacity variables are analogous to mean residence time, which serves as a cost indicator for processes invoi ving reaction. The capacity variables are evaluated for a range of processes separatins binary and ternary mixtures and a range of thermodynamic systems. The capacity variables reflect the impact of the operating parameters, such as product specifications and reflux ratio, on process costs. In distillation processes, the optimum reflux ratio is found to be close to the beuristic value of 1.2 times the minimum reflux ratio. The capacity variables are proposed as useful tools for the initial stages of process synthesis.
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, South Africa in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Separation (Technology); Equilibrium.; Vapor-liquid equilibrium.